Plant trait assembly affects superiority of grazer's foraging strategies in species-rich grasslands - Mládek, Jan; Mládková, Pavla; Hejcmanová, Pavla; Dvorský, Miroslav; Pavlu, Vilém; De Bello, Francesco; Duchoslav, Martin; Hejcman, Michal; Pakeman, Robin J (PLoS One, 2013)
BACKGROUND: Current plant--herbivore interaction models and experiments with mammalian herbivores grazing plant monocultures show the superiority of a maximizing forage quality strategy (MFQ) over a maximizing intake strategy (MI). However, there is a lack of evidence whether grazers comply with the model predictions under field conditions. METHODOLOGY/FINDINGS: We assessed diet selection of sheep (Ovis aries) using plant functional traits in productive mesic vs. low-productivity dry species-rich grasslands dominated by resource-exploitative vs. resource-conservative species respectively. Each grassland type was studied in two replicates for two years. We investigated the first grazing cycle in a set of 288 plots with a diameter of 30 cm, i.e. the size of sheep feeding station. In mesic grasslands, high plot defoliation was associated with community weighted means of leaf traits referring to high forage quality, i.e. low leaf dry matter content (LDMC) and high specific leaf area (SLA), with a high proportion of legumes and the most with high community weighted mean of forage indicator value. In contrast in dry grasslands, high community weighted mean of canopy height, an estimate of forage quantity, was the best predictor of plot defoliation. Similar differences in selection on forage quality vs. quantity were detected within plots. Sheep selected plants with higher forage indicator values than the plot specific community weighted mean of forage indicator value in mesic grasslands whereas taller plants were selected in dry grasslands. However, at this scale sheep avoided legumes and plants with higher SLA, preferred plants with higher LDMC while grazing plants with higher forage indicator values in mesic grasslands. CONCLUSIONS: Our findings indicate that MFQ appears superior over MI only in habitats with a predominance of resource-exploitative species. Furthermore, plant functional traits (LDMC, SLA, nitrogen fixer) seem to be helpful correlates of forage quality only at the community level.
Keywords: Linear Models; lipnicovité; biomasa; Quantitative Trait, Heritable; Biomass; Ecosystem; Species Specificity; Herbivory; druhová specificita; dieta; Sheep; ekosystém; Diet; zvířata; býložravci; Animals; ovce; kvantitativní znak dědičný; lineární modely; Poaceae